Teachers’ Perceptions of Personal Wellbeing during the COVID-19 Pandemic: An Exploration of Job Demands and Job Resources - Ganasen, Shenay (University of the Witwatersrand, Johannesburg, 2024)
Teachers are the frontline workers of the education system, and their wellbeing is important for several reasons. Firstly, it is a priority in and of itself. Secondly, it influences the wellbeing and learning of learners (Collie & Martin, 2020; Harding et al., 2019). Lastly, it contributes greatly to the quality of education delivered in schools and hence, the overall success of schools (Chen et al., 2020; Ozamiz-Etxebarria et al., 2021). Therefore, it is important to understand the way in which job characteristics of the teaching environment, such as job demands and job resources, influence teacher wellbeing. While previous literature has examined the influence of job demands and job resources on teacher wellbeing within the South African context, studies concerning the role of the COVID-19 pandemic in relation to teacher wellbeing are scarce. Therefore, this research aimed to explore teachers’ perceptions of wellbeing during the COVID-19 pandemic and the influence that job demands and job resources had on such perceptions. Interviews were conducted with eight teachers in the Johannesburg area to explore their perceptions and experiences of wellbeing, job demands and job resources during the pandemic. The findings of this research suggested that the teachers in this study perceived their wellbeing as compromised during the pandemic. Most of the participants found their job resources to be inadequate in meeting their job demands which seemed to bring about challenges with health, job performance and job satisfaction. The findings were supported by the JD-R Theory which shows the way in which a negative imbalance between job demands and job resources impacts health, satisfaction and hence, overall employee wellbeing. The implications and limitations of the study are discussed and recommendations for future research are made.
A research report submitted in fulfillment of the requirements for the Master of Education (Educational Psychology), In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Job Demands-Resources Theory; teacher wellbeing; COVID-19 pandemic; SDG-4: Quality education